2016
DOI: 10.1037/dev0000191
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender differences in ability emotional intelligence in adults: A cross-sectional study.

Abstract: The goal of the current investigation was to analyze ability emotional intelligence (EI) in a large cross-sectional sample of Spanish adults (N = 12,198; males, 56.56%) aged from 17 to 76 years (M = 37.71, SD = 12.66). Using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT), which measures ability EI according to the 4 branches of the Mayer and Salovey EI model. The authors examined effects of gender on ability EI, as well as the linear and quadratic effects of age. Results suggest that gender affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
113
4
26

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 35 publications
17
113
4
26
Order By: Relevance
“…However, other authors do not find significant association between age and EI ability [48,49]. According to these data, EI increases with time, but declines with age as any other cognitive ability [50]. It is probable that from childhood until adulthood people develop emotional abilities but that cognitive deterioration affects EI.…”
Section: Mobile Emotional Intelligence Test (Meit): a New Way Of Evalmentioning
confidence: 76%
“…However, other authors do not find significant association between age and EI ability [48,49]. According to these data, EI increases with time, but declines with age as any other cognitive ability [50]. It is probable that from childhood until adulthood people develop emotional abilities but that cognitive deterioration affects EI.…”
Section: Mobile Emotional Intelligence Test (Meit): a New Way Of Evalmentioning
confidence: 76%
“…This may be an artefact of age range of our sample with the vast majority of participants aged between 17 and 25. It is possible rather than a linear association, alexithymia has a quadratic association with age (Cabello, Sorrel, Fernández‐Pinto, Extremera, & Fernández‐Berrocal, ; Parker, Taylor, & Bagby, ). Levels of alexithymia may decrease until roughly middle age and then begin to increase thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Females are more attuned to their emotions and studies have confirmed that they may present more emotional intelligence attributes than men (Cabello, Sorrel, Fernandez-Pinto, Extremera, & Fernandez-Berrocal, 2016). Research has indicated that they may seek emotional support when required as they have a good capacity in perceiving, understanding and managing emotions (Cabello et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated that they may seek emotional support when required as they have a good capacity in perceiving, understanding and managing emotions (Cabello et al, 2016). Consequently, it is not surprising that women are more culturally empathic than men.…”
Section: Discussionmentioning
confidence: 99%